Multidrug resistance in ocular melanoma. Issue 11 (November 1996) - McNamara, M; Clynes, M; Dunne, B; NicAmhlaoibh, R; Lee, W R; Barnes, C; Kennedy, S M
Abstract : AIMS/BACKGROUND: Metastatic disease in patients with ocular melanoma is resistant to chemotherapy. One of the main mechanisms of modulating multidrug resistance is the expression of the multidrug resistance gene 1 (MDR1) product (p-glycoprotein) by tumour cells. The purpose of this study was to evaluate the frequency of expression of the MDR1 gene in ocular melanoma whose primary treatment was surgical excision or enucleation. METHODS: Twelve recent ocular melanomas were received fresh, snap frozen and cryostat sections of tumour were analysed for expression of MDR1 by immunohistochemistry using a well characterised monoclonal antibody to MDR1. Tumour explants were established in short term tissue culture from four tumours and cell blocks were examined by immunohistochemistry. RESULTS: MDR1 expression was present in five of 12 ocular melanomas. Upregulation of protein expression was found in four cell lines established in short term culture from tumour explants. A recurrent tumour, initially treated by local excision and radioactive plaque, showed overexpression of MDR1 mRNA. CONCLUSIONS: These results suggest that significant level of MDR1 may be intrinsically present in ocular melanomas before exposure to drugs involved in multidrug resistance, and indicate the possible importance of MDR1 in modulating chemoresistance in ocular melanoma. Chemosensitisation may be of potential value in planning adjuvant chemotherapy for patients with metastatic disease.